Microclimate and thermal comfort of urban forms and canyons in traditional and modern residential fabrics in Bandar Abbas, Iran - Dalman, Masoud; Salleh, Elias @ Ilias; Sapian, Abdul Razak; Mohd Tahir, Osman; Dola, Kamariah; Saadatian, Omidreza (Canadian Center of Science and Education, 2011)
Rapid growth of urban population and urban area during the past 30 years in Bandar Abbas city with hot and humid climate has been regarded as the major concern of urban designers and planners. In modern fabric climate response urban design has been ignored. This paper investigates the microclimate principals of two different fabrics in South East of Bandar Abbas using different thermal comfort indices and microclimate assessment of residential urban canyons. Fieldwork studies in two different fabrics indicate that traditional fabric of study area can have good potential to be called a thermal comfort environment if its vegetation and building environment is modified and integrated in the design appropriately. The finding can be used as reference for urban planners and urban designers and municipality experts of the cities which posses the same climate.